1989
DOI: 10.5962/bhl.part.9801
|View full text |Cite
|
Sign up to set email alerts
|

Two new species, nomenclatural changes, and range extensions in Mexican Arceuthobium (Viscaceae)

Abstract: Two new species of Arceuthobium are described as parasites of pines (Pinus) in Mexico: A. yecorense infects several species of pines (Pinus) in eastern Sonora, western Chihuahua, and western Durango; A. oaxacanum is known only from two populations in one locality in southern Oaxaca. Arceuthobium vaginatum subsp. durangense Hawksw. &; Wiens is raised to specific status. This taxon was previously known only in Durango and Sinaloa and is reported here for the first time in Jalisco. Arceuthobium gillii subsp. nigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 5 publications
0
20
2
Order By: Relevance
“…Arceuthobium rubrum occurs primarily in Durango and adjacent Sinaloa, A. oaxacanum is restricted to Oaxaca, and A. yecorense is known from disjunct populations in Chihuahua, Sonora, and Durango. Arceuthobium oaxacanum was first considered a disjunct population of A. rubrum but was later described as a distinct species (Hawksworth and Wiens, 1989). Arceuthobium yecorense was also first described in Hawksworth and Wiens (1989), but based on morphology, it was considered to be most closely related to A. aureum.…”
Section: Arceuthobium Bicarinatum and A Pusillum-this Clade Was Discmentioning
confidence: 99%
See 2 more Smart Citations
“…Arceuthobium rubrum occurs primarily in Durango and adjacent Sinaloa, A. oaxacanum is restricted to Oaxaca, and A. yecorense is known from disjunct populations in Chihuahua, Sonora, and Durango. Arceuthobium oaxacanum was first considered a disjunct population of A. rubrum but was later described as a distinct species (Hawksworth and Wiens, 1989). Arceuthobium yecorense was also first described in Hawksworth and Wiens (1989), but based on morphology, it was considered to be most closely related to A. aureum.…”
Section: Arceuthobium Bicarinatum and A Pusillum-this Clade Was Discmentioning
confidence: 99%
“…Arceuthobium oaxacanum was first considered a disjunct population of A. rubrum but was later described as a distinct species (Hawksworth and Wiens, 1989). Arceuthobium yecorense was also first described in Hawksworth and Wiens (1989), but based on morphology, it was considered to be most closely related to A. aureum. Both ITS and trnL region sequence analyses result in a clade of the two A. oaxacanum accessions (2035 and 4315, Oaxaca) and this clade is sister to A. rubrum (2071, Durango) followed by A.…”
Section: Arceuthobium Bicarinatum and A Pusillum-this Clade Was Discmentioning
confidence: 99%
See 1 more Smart Citation
“…Arceuthohium ruhrwn Hawksw. & Wiens (Ruby dwarf mistletoe, Viscaceae) is a distinct species with reddish to brownish-red plants and shiny fruits and is a common parasite of several pines (Finus spp., Pinaceae, Table 1) in northwestern Mexico (Hawksworth and Wiens, 1965, 1972, 1996Mathiasen et al 2008). When a dwarf mistletoe with brownish red plants and shiny, red fruits was discovered in western Oaxaca on Pimis pseudostrobus Lindley by Dr.…”
mentioning
confidence: 99%
“…However, based on further studies of two populations of A. ruhrwn in Oaxaca, Hawksworth and Wiens concluded that these populations were sufficiently distinct from those in Durango to describe the Oaxaca populations as a new species: A. oaxacanum Hawksw. & Wiens (Hawksworth and Wiens 1989). They separated A. oaxacanwn from A. ruhrwn based primarily on differences in plant size, plant color, length of pistillate spikes.…”
mentioning
confidence: 99%